(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fauzi MA, Hamidy A, Kurniawan N. 2020. Harvesting trends of Amboina box turtles (Cuora amboinensis) seventeen years after listing in Appendix II CITES. Biodiversitas 21: 1142-1148. Among Southeast Asian freshwater turtles, the Amboina box turtle (Cuora amboinensis) held the highest recorded harvesting levels. The large volumes of harvesting influenced its International Union for Conservation of Nature (IUCN) revised the conservation status of C.amboinensis from Near Threatened to Vulnerable in 2000. The Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) also inclusion of Amboina box turtle in Appendix II category. The CITES trade database provided a data set that tracks the legal trade of C. amboinensis in the global market from 2000 to 2017. Before 2005, Malaysia was the largest major supplier of this species to the global market. However, after 2005, Indonesia replaces Malaysia as the biggest exporter. From 2005 to 2014, the data showed that the trade trends already followed the quota of provisions. The trade routes of C amboinensis showed that the USA was the country to which these turtles were most frequently imported (50 times during 2000-2017), while China was still the biggest importer country in terms of quantity (463584 individuals from 2000-2017). The USA re-exported C. amboinensis for the pet trade to several European countries. Vietnam reportedly also re-exported C. amboinensis from Laos. However, Laos has rarely reported the occurrence of export activities to Vietnam. Based on these findings, we were able to understand the dynamics of the C. amboinensis trade globally more clearly, propose several actions deemed necessary for its conservation, and suggest greater on-going coordinated efforts to monitor the trade of this species.